Aprendizagem ativa : uma proposta para o ensino de luz e som - Santos, José Rafael dos (2016)
In this paper, we discuss the application of a teaching unit designed as a form of educational product, to help basic education teachers in the teaching of wave concepts. First, we applied questionnaires that seek a student relationship profile with the school, with teachers, with other classmates and the methodologies used in teaching and learning process, trying to understand what "mobilize". Next, we apply a pre-conceptions test of wave concepts and use a Potentially Significant Teaching Unit (PMTU) for development was employed twelve hours classes. In the development of the sequence, it is possible to use videos, simulations, Peer instructions (PI), problem-issues developed in Modellus and conceptual maps of logical and potentially significantly. The last stage of PMTU is the application of a post-test, whose answers were categorized as satisfactory, unsatisfactory and not answered it possible to compare the relationships established by students between the physical concepts before and after application, even without the use of scientific language, something likely in the pretest. We transform these qualitative data into quantitative, and to pre-test results (notapré) and posttest (notapós) it was possible to calculate the normalized gain in our class, the expression founded by quantitative analysis suggested by Hake (1998) but also we compare the results of qualitative way. As for the ratio of questionnaires were analyzed according to the Theory of Relation to Know Bernard Charlot (2005) by removing "central argument" of responses. The application of the product occurred in the State School Professor Josefa Marques, located in Redondo Well, with 12 students of the second year of high school. The results showed an improvement in the number of correct issues with the interaction between the students, as well as a normalized gain of 0.72 when comparing satisfactory answers the pretest and posttest.